Peningkatan Kadar Hemoglobin Ibu Hamil Anemia dengan Kombinasi Pemberian Tablet Fe dan Madu - Ahmady, Ahmady; Pulungan, Zulhaini Sartika A.; Purnomo, Edi (Politeknik Kesehatan Tanjung Karang, 2021)
The problem for pregnant women is iron anemia. The natural material that contains iron is honey. The study aims to determine the difference in hemoglobin levels in pregnant anemic who are supplemented Fe tablets and honey. Quasi-experimental research with nonrandomized pretest and posttest with control group design. Samples amounted to 30 people with purposive sampling technique. Analysis using paired t-test and independent sample t-test. The hemoglobin levels of anemic pregnant given Fe tablets only increased by 0,31gr/dl (3,21%), while those given Fe tablets and honey increased 1,06gr/dl (12,20%). Combination Fe tablets and honey can be an alternative for increasing hemoglobin in anemic pregnant.Â